Isothermal Fatigue and Creep-Fatigue Interaction Behavior of Nickel-Base Directionally Solidified Superalloy - Haq, A.U.; Yang, X.G.; Shi, D.Q. (Проблемы прочности, 2018)
The creep-fatigue interaction in directionally solidified nickel-base superalloy was analyzed with the modified Chaboche-based unified viscoplasticity constitutive model. The model features the anisotropic material behavior, hardening/ softening, and stress relaxation. Simple low-cyclic fatigue and specified hold time experiments were conducted on a directionally solidified superalloy (DZ125) at temperatures over 760°C. The material parameters were optimized considering its tensile, cyclic and creep behavior with the Levenberg–Marquardt optimization procedure. The model was constructed in FORTRAN and integrated in FEA software UMAT/ABAQUS. The results show that experimental and simulated hysteresis loop size/shape, peak stresses, stress relaxation, and related areas are closely matched. The modified constitutive model was found to be instrumental for revealing the fatigue and creep-fatigue interaction behavior of such materials and can be used for practical applications. Взаимодействие ползучести и усталости в суперсплаве на основе никеля, полученного направленной кристаллизацией, проанализировано с помощью модифицированной унифицированной определяющей модели вязкопластичности Шабоша. Модель характеризует анизотропное поведение материала, упрочнение/разупрочнение и релаксацию напряжений. Эксперименты по определению малоцикловой усталости и времени пребывания выполнены на суперсплаве (DZ125) при температурах выше 760°С. Параметры материала оптимизированы с учетом его поведения при растяжении, циклической нагрузке и ползучести при помощи метода оптимизации Левенберга–Марквардта. Модель построена на языке ФОРТРАН и интегрирована в программу FEА UMAT/ABAQUS. Показано, что экспериментальные и модельные размеры/ форма петли гистерезиса, пиковые напряжения, релаксация напряжений и их область находятся в соответствии. Установлено, что модифицированную определяющую модель целесообразно применять при анализе усталости и взаимодействия ползучести и усталости подобных материалов, она может также найти практическое применение.